Green Ca2La2BO6.5:Pb2+ phosphor: an innovative solution in enhancing the color quality and luminous flux of WLEDs - Phung Ton That; Nguyễn Đoàn Quốc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Light-emitting diodes devices that embedded with multiple chips (multi-chip white LEDs (MCW-LEDs)) are an advanced lighitng solution with much potential for improvement in the lighting industry. However, to further the applicacations and quality of white light emitting diodes (WLEDs) greater achivements must be found, thus, this paper focus on improving the color uniformity and luminous flux with green phosphor Ca2La2BO6.5:Pb2+. The results, which were measured through experiments conducted in WLEDs with average correlated color temperature from 6600–7700 K, show enhancements in color uniformity and luminous efficacy. In particular, the growing trend in the concentration of green phosphor Ca2La2BO6.5:Pb2+ results better color uniformity and lumnous flux, although the color quality scale (CQS) suffers a small decline. Therefore, it is confirmed that the Ca2La2BO6.5:Pb2+ phosphor is suitable in manufacturing WLEDs that focus on the color uniformity and luminous flux.